Intergenerational Social Mobility among Scheduled Caste Families in Haryana - Ekta,; Kaushik, Sushma; Kumar , Kamal; Kishnawat , Lokendra Singh; Bala , Anju (Indian Journal of Extension Education, 2023)
To explore the intergenerational social mobility among scheduled caste families in Hisar district of Haryana state, the study was conducted in the year 2020 with  200 respondents. The results revealed that there has been a significant improvement in the educational qualifications of subsequent generations. Similarly, the occupation distribution of successive generations showed a decreasing proportion of individuals engaged in farm labour and livestock, while an increasing proportion of individuals engaged in non-farm labor, private service, and business. There is a shift in the occupational class distribution of consecutive generations. A strong and positive correlation was found between occupational mobility and factors such as family size, family income, and livelihood status. On the other hand, educational mobility was positively correlated with family size, family income, education status, and information source utilization, but negatively correlated with age. Additionally, social mobility is negatively correlated with livelihood status.